2015
DOI: 10.1016/j.jad.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic mechanisms in depression and anxiety: The role of rumination and attentional control

Abstract: Background Deficits in attentional control have been hypothesized to cause rumination, suggesting that the relationships between attentional control and clinical symptoms may be mediated in part by rumination. However, to date, no clinical study has examined these constructs transdiagnostically in a path analysis model. Methods Fifty-one adults presenting for treatment completed measures of self-reported attentional control, rumination, and depression and anxiety symptoms. A bias-corrected path analysis-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 58 publications
6
79
1
5
Order By: Relevance
“…These relationships are consistent with previous reports stating that acting with awareness is negatively related to anxiety and depression (Bohlmeijer et al, 2010), and it has also been found to be inversely associated with worry and rumination (de Bruin, 2012) which are associated with both social anxiety and depression (Hsu et al, 2015). Being aware of one's present activity may compete for attentional resources required for processing of negative repetitive thoughts (Raphiphatthana et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These relationships are consistent with previous reports stating that acting with awareness is negatively related to anxiety and depression (Bohlmeijer et al, 2010), and it has also been found to be inversely associated with worry and rumination (de Bruin, 2012) which are associated with both social anxiety and depression (Hsu et al, 2015). Being aware of one's present activity may compete for attentional resources required for processing of negative repetitive thoughts (Raphiphatthana et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…worry, rumination) (e.g. Hsu et al, 2015). Thus, we hypothesized that there are significant differences between the levels of describing, nonjudging, acting with awareness and non-reacting facets in the three groups, particularly groups with SAD and MDD show lower levels of these facets as compared to the healthy group.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The exact definition of the transdiagnostic construct per study is provided in Table . Only a minority of constructs (36%) involved multiple processes. Most studies (81%) were descriptive in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Seven participants with PE stated that they had based their evaluation of goal attainment on duration (unspecified) of sexual activity, six participants (three with ED and three with PE) took their partner's orgasm as an indication of success, four participants with ED rated success in terms of a bodily sensation of erection, while four participants with ED could not specify what they had based their judgment on. Table 2 summarizes participants' positive and negative metacognitive beliefs in light of four specific selfreported cognitive-attentional responses: rumination, distraction, worry, and self-imposition (Hsu et al, 2015). Eighteen participants identified positive metacognitive beliefs about the usefulness of their cognitive-attentional response in: (a) enhancing sexual performance (five participants with ED, eight with PE), (b) controlling negative thoughts and emotions (three participants with ED, two participants with PE), and (c) understanding the causes of their sexual problem (three participants with ED).…”
Section: Pursued Goalmentioning
confidence: 99%